Spectrum of root rot (Rhizoctonia solani) incidence in ajwain (Trachyspermum ammi) in southern parts of Rajasthan - FAGODIA, BABU LAL; MALI, B L; TRIVEDI, AMIT; FAGODIYA, R K (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was done with the objective of proper understanding of occurrence and distribution of root rot and subsequent loss assessment in ajwain (Trachyspermum ammi L. ). To have a comprehensive view of the disease severity, diseased fields were surveyed in 40 villages of different districts, viz. Udaipur, Rajsamand, Chittorgarh and Pratapgarh of southern Rajasthan in the year of 2015–16 and 2016–17. The study revealed that the per cent plant mortality ranged in between 12.80–32.50 and 15.00–35.50% at 45 days after sowing (DAS) in both the years, respectively. The maximum and minimum per cent plant mortality was recorded in Bhatewar (Udaipur) and Phoonkiya (Rajsamand) in both the years, respectively. The overall per cent plant mortality was observed more in the year 2016–17 as compared to 2015–16. Losses caused by the root rot disease were studied by incorporating various levels of inoculum densities of Rhizoctonia solani @ 50, 100 and 150 g/plot individually as well as in different combinations in soil before sowing of local susceptible cultivar. The results were compared with uninoculated protected plots and demonstrated that among the treatment, the maximum yield losses (70.90%) were recorded with inoculum @ 150 g/plot followed by inoculum @100 g/plot (47.27%) inoculated plot. The minimum yield losses of 40.85% were observed in plots inoculated @ 50 g/plot with R. solani. The disease was found to cause severe losses on a wide area under ajwain cultivation in southern Rajasthan.